Factors that affect the ability of universities to commercialize their patents in a latin american country - Ramírez Hernandez, Luis Fernando (2020)
The main purpose for this study was to find out which factors at the university level affect the ability to commercialize their invention patents in a Latin American country. Twenty-one Colombian universities participated in this study. The information was treated by the Partial Least Squares regression (PLS) path model. The primary information was obtained from the application of a survey to a random sample of 87 invention patents, whose holder is a Colombian university. Of the answers received, the one that generates the most concern is the fact that almost 80% of patents of invention have not been commercialized. This discovery is new for the Colombian case and it is something for which until now there was no scientific evidence. This not only questions the effectiveness of the country's Innovation System, but also forces to review the processes of scientific research and patenting carried out by universities. It demonstrates weaknesses in academic entrepreneurship to the extent that scientific research is not producing commercial applications capable of generating revenue and incomes for those universities. For its part, the determination level R² values of the endogenous constructs considered substantial the variable Closeness to the market (58.8%) which turns out to be the most determining factor in order to achieve an effective commercialization of patents in this country. This explains the poor ability of Colombian universities to commercialize their patents and it gives the management of innovation and university research the challenge of promoting the "exploitation of knowledge" through three strategies: 1) better market research; 2) strengthening relations with industry; and 3) the prior identification of the real possibilities of commercialization of its innovations.